Palladium-Catalyzed C–H Cyclization in Water: A Milder Route to 2-Arylbenzothiazoles - Inamoto, Kiyofumi; Nozawa, Kanako; Kondo, Yoshinori (Synlett, 2012)
Water was successfully employed as a reaction medium in palladium-catalyzed C–H cyclization of thiobenzanilides. Reactions efficiently proceeded under considerably mild conditions such as 40 °C in water, providing a more practical, greener method for the synthesis of 2-arylbenzothiazoles. For some substrates, the addition of an amphiphilic surfactant greatly enhanced the process. The method represents a rare example of palladium-catalyzed C–H functionalization processes performed in water.
Keywords: palladium; catalysis; heterocycles; water; C–H functionalization